Influence of immunogenetics, sex and body condition on the cutaneous microbial communities of two giant salamanders. Issue 8 (3rd March 2018) - Hernández‐Gómez, Obed; Briggler, Jeffrey T.; Williams, Rod N.
Abstract: The complex association between hosts and microbial symbionts requires the implementation of multiple approaches to evaluate variation in host physiology. Within amphibians, heterogeneity in immunogenetic traits and cutaneous microbiota is associated with variation in disease resistance. Ozark ( Cryptobranchus alleganiensis bishopi ) and eastern hellbenders ( C. a. alleganiensis ) provide a model system to assess variation in host traits and microbial communities. Ozark hellbenders have experienced declines throughout their range, are federally endangered and experience wound retardation that is absent in the eastern subspecies. Previous microbial investigations indicate differentiation in the composition of the skin microbiota of both hellbender subspecies, but it is not clear whether these patterns are concurrent with diversity in the major histocompatibility complex (MHC) genes. We characterized the MHC IIB and the skin microbiota of hellbenders in Missouri, where both subspecies co‐occur though not sympatric. We compared the microbiota composition and MHC diversity between both subspecies and investigated whether individual‐level MHC diversity, sex and body condition were associated with microbiota composition. Overall, MHC IIB diversity was lower in Ozark hellbenders compared to the eastern subspecies. Multivariate statistical comparisons identified microbiota differentiation between Ozark and eastern hellbenders. MHC IIB allele presence/absence, allele divergence, body composition and sex defined grouping of hellbender microbiotas within populations. Differentiation of the cutaneous microbiotas and MHC IIB genes between eastern and Ozark hellbenders suggests that differences exist in immunity between the two subspecies. This study demonstrates how simultaneous assessments of host genetic traits and microbiotas can inform patterns of microbial community structure in natural systems.